PEDAGOGIA DA AUTONOMIA E METODOLOGIAS ATIVAS NO ENSINO SUPERIOR (Functional Plant Breeding Journal, 2021)
This work aims to address active methodologies with a view to the teaching-learning process that ensures a critical view of young people and adults inserted in Higher Education. It was observed, in view of the bibliographical review carried out here, that they deal with active methodologies, proposals that privilege a teaching-learning process based on the pedagogy of autonomy discussed by Paulo Feire. This way of articulating this perspective of autonomy in active methodologies is promising for adding a more dynamic, creative character and a sense of self-government over the knowledge construction process. Thus, the bibliographic survey discussed throughout the text articulates these forms of methodologies as a promising dialogue to rethink traditional teaching-learning methodologies.